Two-pore channels for integrative Ca signaling. - Zhu, M; Evans, A; Ma, J; Parrington, J; Galione, A (2010)
Two-pore channels (TPCs) are related to voltage-gated Ca(2+) and Na(+) channels. They most likely work as dimers with each of the two TPC protein subunits containing two pore-forming domains. Recent studies suggest that TPCs are expressed on the membranes of endosomes and lysosomes where they form receptors for nicotinic acid adenine dinucleotide phosphate (NAADP), the most potent Ca(2+) mobilizing messenger inside cells. Upon activation by NAADP, Ca(2+) release from endolysosomal stores through TPCs triggers cytoplasmic Ca(2+) signals. Because of discrete localizations of these acidic vesicles and their small, albeit variable, sizes, the Ca(2+) signals from endolysosomes are local and, perhaps, represent unique elementary Ca(2+) events. These localized signals can be converted into regenerative global Ca(2+) waves by triggering Ca(2+)-induced Ca(2+) release from endoplasmic reticulum. We will discuss the implications of these findings and the significance of TPCs in integrative Ca(2+) signaling in animal cells.